We GET Vegetables: Learning Application of Vegetables - Liew, Jia Yu; Murli, Norhanifah (Applied Information Technology And Computer Science, 2023)
Vegetables are important for children’s health but most of them are dislike to eat vegetables and it causes them lack of interest to learn vegetables’ names. Moreover, most green vegetables which are similar in colour and shape are out of the school syllabus. Hence, We GET Vegetables learning application that use gamification approach is developed for Chinese primary school students ages seven to nine years old to learn about types of vegetables. This application contains three modules which are learning module, quiz module, and game module. The ADDIE Model is used as methodology, while Unity and C# programming language are used to develop the application. The level of user acceptance is high with 90.3% positive feedback by using the System Usability Scale (SUS). The objectives of this project have been achieved and some improvements that could be made in the future to enhance the application are suggested.